AVAILABILITY OF SPECIAL TREATMENTS AND SERVICES FOR INDIVIDUALS WITH AUTISM SPECTRUM DISORDERS DURING COVID-19 STATE OF EMERGENCY AND LOCKDOWN IN SERBIA - Stojanović, Aleksandra; Stanković, Miodrag (Acta medicae Medianae, 2023)
Restrictive measures and major lifestyle changes were brought for entire population during the beginning of the COVID-19 pandemic, and for individuals with Autism Spectrum Disorder (ASD) and their caregivers as well. Specialized treatments, organized education, and other services intended for the ASD population ceased, which affected overall functioning of this population and their caregivers. ASD itself significantly affects lives of individuals with this disorder and their families, and these individuals are particularly sensitive to changes in routines and daily functioning. The aim of this study was to explore changes in different treatments and services availability for individuals with ASD in Serbia at the beginning of the pandemic and during the state of emergency, and its impact on their caregivers. Participants completed the "Autism and COVID-19" survey, which was designed for primary caregivers of individuals with ASD. A sample of 89 participants completed the survey. They were recruited from patient databases, the parents’ association (NGOs), and the specialized schools. The study was conducted during the state of emergency in the country, from April 13 to 25, 2020. The survey revealed a complete absence of specialized treatments, lack of support, feelings of helplessness of the caregivers, which have become more prominent during emergency state. The pandemic reveals underdeveloped strategies to maintain support for this population, and the need for better predictions in the future to protect this vulnerable population and their caregivers.